Frozen Food Business Strategy Analysis “ UD. Fresh Frozen Food ” With 10 Types Of Innovation And Business Model Canvas - Ismatul Hasanah; Indria Dwi Hapsari; Imam Arifi (Jurnal Ekonomi, 2024)
Between 2022 and 2024, frozen businesses will experience a year-on-year increase in transactions. However, this is different from UD. fresh frozen foods, which will experience a decline between 2022 and 2024. Due to this trend, it is important for companies to develop new ideas. Finding the business model canvas that will be used after implementing ten types of innovation strategies, ten types of innovation strategies that have been implemented, and ten types of new innovation strategies is the aim of this research. This research uses descriptive methodology and qualitative research techniques. After carrying out 10 different forms of innovation, research findings identified nine components of the UD. fresh frozen food canvas business model. Additionally, ten types of UD. fresh frozen food innovation strategies—cost leadership, flexible manufacturing, product excellence, community, and ownership—were identified. The results of this strategy are new and appropriate for UDfresh frozen foods, including cost leadership, predictive analytics, superior products, loyalty programs and process automation. Apart from helping UD. Fresh Frozen Food is expanding its frozen business with the Fresh Frozen Food brand, this research can be a source for entrepreneurs who want to innovate in their business tactics. from the results of this research, UD fresh frozen food uses the canvas business model as an effective tool for designing and managing a business by describing key elements that are interrelated, with a systematic approach such as input-output analysis, this research is very useful for helping companies in creating models a business that is efficient, sustainable and responsive to market needs